Thermal Annealing Influence on Spectral Responsively and Specific Detectivity for Al/NiO/PSi/Si/Al Photodetectors - Muhammid H. AL-Baghdadi, Esraa H. Hadi, Hiba Noori Thakir, Nadir F. Habubi (International Journal of Advanced Science and Technology, 2020)
Al/p-NiO/PSi/n-Si/Al sandwich structure was synthesis and studied utilizing  drop casting method DCM . NiO NPs subjected to thermal annealing at (250 and 500)°C, NiO thin films show a decreases in the energy bandgap from 3.5eV to2.9eV, which  was calculated from optical properties. AFM images of  NiO films confirm a ball-shape with perfect homogeneity, the measurements of XRD revealed that NiO were cubic crystal structure, the spectral responsivity and specific detectivity of  photodetector after annealing showed an increasing and enhancing in characterization of porous silicon in response.